Interactions of Corporate Financing and Investment Decisions: A Dynamic Framework - MAUER, DAVID C.; TRIANTIS, ALEXANDER J. (Journal of Finance, 1994)
ABSTRACT This article analyzes the interaction between a firm's dynamic investment, operating, and financing decisions in a model with operating adjustment and recapitalization costs. Using numerical analysis, we solve the model for cases that highlight interaction effects. We find that higher production flexibility (due to lower costs of shutting down and reopening a production facility) enhances the firm's debt capacity, thereby increasing the net tax shield value of debt financing. While higher financial flexibility (resulting from lower recapitalization costs) has a similar effect, production flexibility and financial flexibility are, to some extent, substitutes. We find that the impact of debt financing on the firm's investment and operating decisions is economically insignificant.